Jaguar and Puma Attacks on Livestock in Costa Rica - Ronit Amit; Elias José Gordillo-Chávez; Raquel Bone (Human-Wildlife Interactions, 2017)
Human–felid conflicts threaten long-term conservation of jaguars (Panthera onca) and pumas (Puma concolor). We interviewed ranchers from 50 ranches and inspected farms in northern Costa Rica that reported recent attacks on livestock by these 2 felids. We analyzed ranch characteristics, livestock management practices, details of predation, estimated market-value of economic losses, and ranchers’ perception of damage. Ranchers reported 81 felid attacks on livestock, including 60 head of cattle, 16 horses, 3 sheep, 1 pig, and 1 goat. Mean size of ranches was 233 km2, and mean livestock herd size was 109, including cattle, horses, pigs, sheep, goats, and water buffalo (Bubalus bubalis). Mean value of an attacked animal was U.S. $177.75 (range = $15 to $854, n = 51), and cumulative loss for all cattle was U.S. $9,065. Eighty-four percent of ranchers reported the presence of jaguars on their property, and 36% perceived the presence of pumas. Economic losses were overestimated by ranchers. Management strategies to address these problems must take into account the small size of ranches and limitations of the cattle and livestock production system in Costa Rica. Damage quantification based on market values can provide a guide to establish an incentive program, but provisions are needed due to ranchers’ potential discontent. The results of this study form the basis of Costa Rica’s current technical assistance projects, as well as provide a protocol to evaluate reports of jaguar and puma attacks on domestic animals in the country.